2012
DOI: 10.1177/1049909112457011
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life and Palliative Care Education in US Pharmacy Schools

Abstract: The objective of this endeavor was to ascertain the current status of end-of-life and palliative care within the curriculum of US pharmacy schools and compare to a similar 1986 study. Additionally, responses to recent professional guidelines for pharmacy schools regarding end-of-life issues can be addressed. A fixed-choice survey was mailed to the 125 US pharmacy schools with a 49% response rate. Results revealed that the lecture format of teaching on end-of-life issues continues to be used today with an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…10 Research performed with different students and health professionals showed that: nurses with education in palliative care had less difficulty talk about death and did not refer to fearing death; 20 human service students who had contact with an education about death presented a reduction in anxiety when faced with death compared to students who had no education on the subject; 21 pharmacy students, who had access to education about death through simulation in clinical skills laboratories , demonstrated a significant improvement in their attitudes towards death compared to pre-simulation and declared themselves more competent to care for patients in the process of death; and that the study of death for undergraduate pharmacy student had been of real importance and had led to curricular improvement. [22][23] Considering the cited studies, the importance of an education regarding the subject of death and dying, so that the professional is prepared to exercise his profession with quality is considered justified.…”
Section: Discussionmentioning
confidence: 99%
“…10 Research performed with different students and health professionals showed that: nurses with education in palliative care had less difficulty talk about death and did not refer to fearing death; 20 human service students who had contact with an education about death presented a reduction in anxiety when faced with death compared to students who had no education on the subject; 21 pharmacy students, who had access to education about death through simulation in clinical skills laboratories , demonstrated a significant improvement in their attitudes towards death compared to pre-simulation and declared themselves more competent to care for patients in the process of death; and that the study of death for undergraduate pharmacy student had been of real importance and had led to curricular improvement. [22][23] Considering the cited studies, the importance of an education regarding the subject of death and dying, so that the professional is prepared to exercise his profession with quality is considered justified.…”
Section: Discussionmentioning
confidence: 99%
“…A 2013 survey-based study found 82% of pharmacy schools (N561 respondents, 49% response rate) reported offering palliative care or end-of-life education. 14 This was a small increase from a 2003 study with a similar design. 15 Both studies noted only an average of 6 hours of curriculum time devoted to this material.…”
mentioning
confidence: 91%
“…34,35 Attesting to the importance of this topic in the training of pharmacists, the average number of didactic hours devoted to palliative care in U.S. schools of pharmacy increased from a mean of 3.89 in 2001 to 6.24 in 2012. 35,36 While 82% of responding schools reported end-of-life and palliative care topics covered within their curriculum, it remains unclear to what extent symptom management is covered within these programs.…”
Section: Introductionmentioning
confidence: 99%